Host methylglyoxal activates the Listeria virulence program, allowing bacteria to evade inflammatory phagocytes by cell-to-cell spread - Andrea Anaya-Sanchez; Preethi T. Ragunathan; Angela Hung; Andrew J. Van Alst; Mariya Lobanovska; Sarah A. Stanley; Daniel A. Portnoy (Proceedings of the National Academy of Sciences, 2026)
Methylglyoxal is a reactive aldehyde produced by macrophages as part of their antimicrobial innate immune arsenal. Our prior work showed that Listeria monocytogenes relies on glyoxalase A (GloA) and bacterial glutathione to detoxify methylglyoxal and that loss of GloA severely impairs bacterial virulence in mice and results in a 100 to 1,000 increase in bacterial mutation frequency. Glutathione is required for both methylglyoxal detoxification and for allosteric activation of the master virulence regulator PrfA, underscoring its central, yet complicated role in pathogenesis. We previously demonstrated that mutations that lock PrfA in its active conformation (PrfA*) rescue the virulence of gloA mutants. Here, we show that PrfA* not only restores virulence but also rescues the elevated mutation frequency of gloA mutants independently of canonical DNA repair pathways. We hypothesized that a PrfA-regulated gene mediates a GloA-independent mechanism to avoid the toxic effects of methylglyoxal and found that the absence of ActA abolished the PrfA*-mediated rescue of gloA mutations. In addition, loss of ActA in a wild-type background also increased the in vivo mutation frequency of L. monocytogenes . Since the primary role of ActA is to mediate bacterial cell-to-cell spread, we hypothesized that ActA allows L. monocytogenes to migrate away from MG-rich inflammatory foci populated by activated macrophages. Indeed, antibody depletion of elicited macrophages and neutrophils rescued the virulence defect and reduced mutation frequency of gloA mutants. We propose a model in which ActA-mediated actin-based motility allows L. monocytogenes to spatially evade localized methylglyoxal production and hence outrun host defenses.